2004
DOI: 10.1520/jfs2003312
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Stutter Percentages and Allele Peak Height and Peak Area Ratios at Heterozygous STR Loci for Forensic Casework and Database Samples

Abstract: To assist the interpretation of STR DNA typing results from forensic casework samples containing mixtures, the range of heterozygous allele peak height and peak area ratios (HR) and stutter percentages (stutter %) for the loci comprised in the AmpF STR R Profiler Plus TM (PP) kit were assessed on 468 database and 275 casework single source samples. Stutter % medians were similar for database and casework samples, ranging from 2% to 7%. The upper limit of the stutter value range was 16%, calculated as median +3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 23 publications
5
28
0
1
Order By: Relevance
“…Use of a uniform high stutter cut-off value across all markers is a conservative approach, and in the context of HCT, will result in decreased sensitivity to identify low-level chimerism. This study also confirmed results from a previous study that markers labeled with the NED dye had lower median stutter as compared with markers labeled with the JOE or FAM dyes (7). This supports the hypothesis that the repeat structure in the markers labeled with the JOE/FAM dyes may be associated with higher stutter.…”
Section: Discussionsupporting
confidence: 90%
“…Use of a uniform high stutter cut-off value across all markers is a conservative approach, and in the context of HCT, will result in decreased sensitivity to identify low-level chimerism. This study also confirmed results from a previous study that markers labeled with the NED dye had lower median stutter as compared with markers labeled with the JOE or FAM dyes (7). This supports the hypothesis that the repeat structure in the markers labeled with the JOE/FAM dyes may be associated with higher stutter.…”
Section: Discussionsupporting
confidence: 90%
“…The use of peak height imbalance thresholds other than the commonly used 70% is not novel (e.g., Moretti et al use a peak height ratio as low as 59% [8]), and the new versions of commonly used DNA analysis software allow for the incorporation of magnitude-specific peak height thresholds just like those supported by the analysis presented here. For instance, Applied Biosystems GeneMapper® ID-X allows for the use of multiple peak height thresholds based on the heights of the observed peaks.…”
Section: Discussionmentioning
confidence: 99%
“…STR typing typically involves a polymerase chain reaction (PCR) amplification step followed by size fractionation of the resulting products and fluorescent signal detection and processing. Numerous studies have shown that the signal associated with each allele of a heterozygote at a given locus is approximately equal [3][4][5][6][7][8][9]. General practice has shown that the peak height ratio, as measured by dividing the height (in relative fluorescent units (RFUs)) of the lower quantity allele by the height of the higher quantity allele "should be greater than approximately 70% in a single source sample" [3].…”
Section: Introductionmentioning
confidence: 99%
“…Armonk, NY: IBM Corp.) were used to illustrate differences of peak balance (also peak height ratio or heterozygote balance). Peak balance was calculated for each heterozygous combination (at least five individuals per allele combination) according to Method #2, developed by Leclair et al (2004), and defined as the ratio of peak height of the longer allele over that of the shorter allele. For comparison of allele sizes standard deviation and range were calculated for each marker using Microsoft Excel (2010).…”
Section: Discussionmentioning
confidence: 99%